Social science for conservation in working landscapes and seascapes - Bennett, Nathan J.; Dodge, Molly; Akre, Thomas S.; Canty, Steven W. J.; Chiaravalloti, Rafael; Dayer, Ashley A.; Deichmann, Jessica L.; Gill, David; McField, Melanie; McNamara, James; Murphy, Shannon E.; Nowakowski, A. Justin; et al. (Frontiers in Conservation Science, 2022)
Biodiversity is in precipitous decline globally across both terrestrial and marine environments. Therefore, conservation actions are needed everywhere on Earth, including in the biodiversity rich landscapes and seascapes where people live and work that cover much of the planet. Integrative landscape and seascape approaches to conservation fill this niche. Making evidence-informed conservation decisions within these populated and working landscapes and seascapes requires an in-depth and nuanced understanding of the human dimensions through application of the conservation social sciences. Yet, there has been no comprehensive exploration of potential conservation social science contributions to working landscape and seascape initiatives. We use the Smithsonian Working Land and Seascapes initiative – an established program with a network of 14 sites around the world – as a case study to examine what human dimensions topics are key to improving our understanding and how this knowledge can inform conservation in working landscapes and seascapes. This exploratory study identifies 38 topics and linked questions related to how insights from place-based and problem-focused social science might inform the planning, doing, and learning phases of conservation decision-making and adaptive management. Results also show how conservation social science might yield synthetic and theoretical insights that are more broadly applicable. We contend that incorporating insights regarding the human dimensions into integrated conservation initiatives across working landscapes and seascapes will produce more effective, equitable, appropriate and robust conservation actions. Thus, we encourage governments and organizations working on conservation initiatives in working landscapes and seascapes to increase engagement with and funding of conservation social science.